Conservatism Negatively Predicts Creativity: A Study Across 28 Countries - (:unkn) unknown (SAGE Publications, 2024)
Previous studies have found a negative relationship between creativity and conservatism. However, as these studies were mostly conducted on samples of homogeneous nationality, the generalizability of the effect across different cultures is unknown. We ad...
Keywords: Conservadurismo; Creatividad